Dissecting the roles of TRBP and PACT in double‐stranded RNA recognition and processing of noncoding RNAs. (28th January 2015) - Heyam, Alex; Lagos, Dimitris; Plevin, Michael
Abstract : HIV TAR RNA‐binding protein (TRBP) and Protein Activator of PKR (PACT) are double‐stranded (ds) RNA‐binding proteins that participate in both small regulatory RNA biogenesis and the response to viral dsRNA. Despite considerable progress toward understanding the structure–function relationship of TRBP and PACT, their specific roles in these seemingly distinct cellular pathways remain unclear. Both proteins are composed of three copies of the double‐stranded RNA‐binding domain, two of which interact with dsRNA, while the C‐terminal copy mediates protein–protein interactions. PACT and TRBP are found in a complex with the endonuclease Dicer and facilitate processing of immature microRNAs. Their precise contribution to the Dicing step has not yet been defined: possibilities include precursor recruitment, rearrangement of dsRNA within the complex, loading the processed microRNA into the RNA‐induced silencing complex, and distinguishing different classes of small dsRNA. TRBP and PACT also interact with the viral dsRNA sensors retinoic acid‐inducible gene I (RIG‐I) and double‐stranded RNA‐activated protein kinase (PKR). Current models suggest that PACT enables RIG‐I to detect a wider range of viral dsRNAs, while TRBP and PACT exert opposing regulatory effects on PKR. Here, the evidence that implicates TRBP and PACT in regulatory RNA processing and viral dsRNA sensing is reviewed and discussed in the context of their molecular structure. The broader implications of a link between microRNA biogenesis and the innate antiviral response pathway are also considered. WIREs RNA 2015, 6:271–289. doi: 10.1002/wrna.1272 This article is categorized under: RNA Interactions with Proteins and Other Molecules > Protein–RNA Interactions: Functional Implications RNA Turnover and Surveillance > Turnover/Surveillance Mechanisms Regulatory RNAs/RNAi/Riboswitches > Biogenesis of Effector Small RNAs